The immunopathology of sepsis and potential therapeutic targets - van der Poll, Tom; van de Veerdonk, Frank L.; Scicluna, Brendon P.; Netea, Mihai G. (Nature reviews. Immunology, 2017)
Key Points Sepsis is a life-threatening organ dysfunction that is caused by a dysregulated host response to infection. The sepsis-associated host response is characterized by concurrent excessive inflammatory, catabolic, metabolic and immune-suppressive features, and a failure to return to homeostasis, which often results in a condition referred to as chronic critical illness and is not fundamentally different from the sustained host response aberrations that are induced by severe non-infectious injuries. Sepsis is a very heterogeneous syndrome, and current knowledge does not enable the stratification of patients into more homogeneous subgroups in which specific and potentially targetable host response derailments drive pathology. Key pro-inflammatory responses during sepsis include the activation of the complement system, the coagulation system, the vascular endothelium, neutrophils and platelets, whereas immune suppression is primarily caused by the reprogramming of antigen-presenting cells, and the apoptosis and exhaustion of lymphocytes. Individuals who survive sepsis frequently suffer from long-term cognitive and physical impairments, the aetiology of which is uncertain. Strategies to modulate the aberrant host response have been unsuccessful in a large number of clinical trials, which may at least in part be related to the inadequate selection of therapeutic targets and an inability to select the patients who might benefit from a certain intervention. Future research should focus the discovery and validation of biomarkers that reflect the predominant pathophysiological mechanisms at different body sites, and that can guide the selection of patients for targeted therapies and the monitoring thereof. Sepsis — which is caused by a dysregulated host response to infection — is a life-threatening organ dysfunction. This Review describes the recent advances in our understanding of sepsis pathogenesis and discusses strategies for the development of successful therapies. Sepsis is defined as a life-threatening organ dysfunction that is caused by a dysregulated host response to infection. In sepsis, the immune response that is initiated by an invading pathogen fails to return to homeostasis, thus culminating in a pathological syndrome that is characterized by sustained excessive inflammation and immune suppression. Our understanding of the key mechanisms involved in the pathogenesis of sepsis has increased tremendously, yet this still needs to be translated into novel targeted therapeutic strategies. Pivotal for the clinical development of new sepsis therapies is the selection of patients on the basis of biomarkers and/or functional defects that provide specific insights into the expression or activity of the therapeutic target.